РУЎХЫЙ ЖЕТИКЛИК ҲӘМ ОҒАН ЕРИСИЎ ЖОЛЛАРЫ - Сейтов, М. (SCIENCE and SOCIETY, 2020)
Spirituality is the nature of a man himself. Spirituality is both thinking, and consciousness, and the will of man, this is a single integral factor, peculiar to a man. Man is intimately connected with the universe. Spirituality is what is absent in nature. Spirituality gives us access to love, conscience, a sense of duty, to justice and statehood, to art, science and religion, indicates what is the main and most valuable thing in life.